Shared Roles and Responsibilities of Older Adults in Jaffna, Sri Lanka: Unrecognized Contributions to Their Families and Communities - Shamila, S.; Jeevasuthan, S. (Oxford University Press, 2023)
This chapter focuses on a qualitative study with 20 older adults and their family members who are from different economic backgrounds in Jaffna District in northern Sri Lanka. The participants were members of the Church of American Ceylon Mission of Sri Lanka. This study was conducted to shed light on the unacknowledged roles and contributions of older adults in a Sri Lankan Tamil Indigenous community. It is significant that Indigenous older adults contributed to the well-being of their families and communities in many ways but were rarely recognized and appreciated by the younger generation. Due to the impact of globalization, Indigenous family systems are changing, and a nuclear family system is being adopted. The study showed that the Indigenous elderly contributed to their families by looking after their grandchildren and taking on responsibility for household chores. Some of the older persons financially supported their children by giving some or all of their pensions to them. Some participants stated that they sold their own properties to support their adult children. Their children believed that in their community, looking after the grandchildren is traditionally performed by grandparents. The adult children, reported older adult participants, did not value their parents’ contributions because they believed that their parents depended on them.
Keywords: Older adults; Indigenous families; Older adult contributions; Sri Lanka; Quality of life